Environment-friendly glass material
An environmentally friendly glass composition with SiO2, ZnO, and alkali metal oxides addresses the issues of cadmium toxicity and stability in selenocadmium glass, offering effective ultraviolet/visible light cutoff and high near-infrared transmittance for smart devices.
Patent Information
- Application Number
- JP2024176916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-06-30
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-05-12
AI Technical Summary
Conventional selenocadmium glass used for near-infrared detection in smart devices is environmentally harmful due to cadmium content and has low chemical stability, making it unsuitable for harsh environments.
A glass composition comprising SiO2, ZnO, alkali metal oxides, and S, with specific ratios and thickness, achieving ultraviolet/visible light cutoff and high near-infrared transmittance without cadmium, and enhanced chemical stability.
The environmentally friendly glass material provides effective ultraviolet/visible light cutoff and high near-infrared transmittance, with improved chemical stability and resistance to harsh environments.
Smart Images

Figure 2025001031000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass material, and more particularly to an environmentally friendly glass material that has ultraviolet and visible light blocking properties and high near-infrared transmittance. [Background technology]
[0002] In recent years, with the development of the optoelectronics industry, the use of near-infrared wavelength band detection from 800nm to 2000nm has become increasingly important, especially in smart devices. Near-infrared lasers are urgently needed for real-time sensing of the surrounding environment to determine the operation and movement of smart devices. Its implementation is based on the fact that optical systems need to eliminate ultraviolet and visible light bands that interfere with the near-infrared operating band, and therefore require higher transmittance in the near-infrared band.
[0003] Conventional selenocadmium glass can cut off ultraviolet and visible light bands and has higher near-infrared transmittance. Its disadvantage is that it contains a lot of cadmium (Cd), which does not meet current environmental standards and causes great harm to the environment and human body during its manufacturing, use and disposal. In addition, selenocadmium glass has low chemical stability and is not suitable for smart devices that need to withstand harsh environments. Summary of the Invention [Problem to be solved by the invention]
[0004] The technical problem to be solved by the present invention is to provide an environmentally friendly glass material that has ultraviolet and visible light blocking properties and high near-infrared transmittance. [Means for solving the problem]
[0005] The technical solutions adopted in the present invention to solve the technical problems are as follows: (1) An environmentally friendly glass material which contains components such as SiO2, ZnO, alkali metal oxides and S, but does not contain Cd, and which has a cutoff wavelength of 550 nm or more, a transmittance of 75% or more at 800 to 850 nm, a transmittance of 80% or more at 850 to 900 nm, a transmittance of 83% or more at 900 to 1000 nm, and a transmittance of 85% or more at 1000 to 2000 nm when the thickness of the environmentally friendly glass material is 3 mm. (2) The environmentally friendly glass material according to (1), wherein when the thickness of the environmentally friendly glass material is 3 mm, the cutoff wavelength is 600 nm or more, preferably 650 nm or more, more preferably 680 nm or more, and even more preferably 700 nm or more. (3) The environmentally friendly glass material according to (1), which has a transmittance of 77% or more at 800 to 850 nm, preferably 80% or more at 800 to 850 nm, when the environmentally friendly glass material has a thickness of 3 mm. (4) The environmentally friendly glass material according to (1), which has a transmittance of 82% or more at 850 to 900 nm, preferably 83% or more at 850 to 900 nm, when the environmentally friendly glass material has a thickness of 3 mm. (5) The environmentally friendly glass material according to (1), which has a transmittance of 84% or more at 900 to 1000 nm, preferably 85% or more at 900 to 1000 nm, when the environmentally friendly glass material has a thickness of 3 mm. (6) The environmentally friendly glass material according to (1), which has a transmittance of 86% or more at 1000 to 2000 nm, preferably 87% or more at 1000 to 2000 nm, when the environmentally friendly glass material has a thickness of 3 mm. (7) An environmentally friendly glass material according to (1), the components of which are expressed in weight percent: SiO2 35-80%; ZnO 5-35%; Na2O 5-25%; K2O 1-10%; S 0.2-8%; and Sb+Ag+Ce+Sn+Te+V+Fe 0.5-10%. (8) An environmentally friendly glass material according to (7), the components of which are expressed in weight percent, further comprising: 0 to 5% Li2O; and / or 0 to 10% B2O3; and / or 0 to 5% Al2O3; and / or 0 to 5% MgO; and / or 0 to 5% CaO; and / or 0 to 10% SrO; and / or 0 to 10% BaO; and / or 0 to 5% Se; and / or 0 to 5% F. (9) An environmentally friendly glass material whose components, expressed in weight percent, are: SiO2 35~80%; ZnO 5~35%; Na2O 5~25%; K2O 1~10%; Li2O 0~5%; S; Sb+Ag+Ce+Sn+Te+V+Fe 0.5~10%; B2O3 0~10%; Al2O3 0%~5%; MgO 0~5%; CaO 0~5%; SrO 0~10%; BaO 0~10%; Se 0~5%; F 0~5% and no Cd. (10) An environmentally friendly glass material according to any one of (1) to (9), the components of which are expressed in weight % and which contain: 40 to 75% SiO2; and / or 7 to 30% ZnO; and / or 7 to 22% Na2O; and / or 2 to 8% K2O; and / or 0 to 3% Li2O; and / or 0.5 to 7% S; and / or 0.8 to 9% Sb+Ag+Ce+Sn+Te+V+Fe; and / or 0 to 5% B2O3; and / or 0 to 3% Al2O3; and / or 0 to 3% MgO; and / or 0 to 3% CaO; and / or 0 to 5% SrO; and / or 0 to 5% BaO; and / or 0 to 5% Se; and / or 0 to 3% F. (11) An environmentally friendly glass material according to any one of (1) to (9), the components of which are expressed in weight % and which contain: 42 to 73% SiO2; and / or 9 to 25% ZnO; and / or 8 to 19% Na2O; and / or 3 to 7% K2O; and / or 1 to 6% S; and / or 0.9 to 8% Sb+Ag+Ce+Sn+Te+V+Fe; and / or 0 to 3% Se; and / or 0 to 2% Li2O; and / or 0 to 3% B2O3; and / or 0 to 1% Al2O3; and / or 0 to 2% MgO; and / or 0 to 2% CaO; and / or 0 to 2% SrO; and / or 0 to 2% BaO; and / or 0 to 1% F. (12) An environmentally friendly glass material according to any one of (1) to (9), the components of which are expressed in weight percent: CuO+TiO2+P2O5 is 0 to 0.5%; preferably CuO+TiO2+P2O5 is 0.0001 to 0.5%; more preferably CuO+TiO2+P2O5 is 0.0001 to 0.4%; and even more preferably CuO+TiO2+P2O5 is 0.0001 to 0.3%. (13) An environmentally friendly glass material according to any one of (1) to (9), in which the components are expressed in weight percent, and B2O3 / SiO2 is 0.23 or less, preferably B2O3 / SiO2 is 0.15 or less, and more preferably B2O3 / SiO2 is 0.1 or less. (14) An environmentally friendly glass material according to any one of (1) to (9), wherein the components are expressed in weight percent, and the ZnO / SiO2 ratio is 0.07 to 0.95, preferably 0.10 to 0.75, and more preferably 0.15 to 0.60. (15) An environmentally friendly glass material according to any one of (1) to (9), wherein the components are expressed in weight percent and the Se / S ratio is 1.5 or less, preferably 1.3 or less, more preferably 1.0 or less, and even more preferably 0.5 or less. (16) The environmentally friendly glass material according to any one of (1) to (9), wherein the components are expressed in weight %, and (Sb+Ag+Ce+Sn+Te+V+Fe) / (Se+S) is 0.1 to 25.0, preferably (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is 0.2 to 15.0, more preferably (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is 0.5 to 8.0, and even more preferably (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is 1.0 to 5.0. (17) The environmentally friendly glass material according to any one of (1) to (9), wherein the components are expressed in weight percent, and (Ag+Ce+Sn+Te+V+Fe) / Sb is 3.0 or less, preferably (Ag+Ce+Sn+Te+V+Fe) / Sb is 2.0 or less, more preferably (Ag+Ce+Sn+Te+V+Fe) / Sb is 1.0 or less, and even more preferably (Ag+Ce+Sn+Te+V+Fe) / Sb is 0.8 or less. (18) An environmentally friendly glass material according to any one of (1) to (9), wherein the components are expressed in % by weight, and Li2O+Na2O+K2O is 8 to 35%, preferably Li2O+Na2O+K2O is 9 to 30%, and more preferably Li2O+Na2O+K2O is 10 to 22%. (19) An environmentally friendly glass material according to any one of (1) to (9), which is free of B2O3; and / or free of Li2O; and / or free of Sn; and / or free of Te. (20) The environmentally friendly glass material according to (9), wherein when the thickness of the environmentally friendly glass material is 3 mm, the cutoff wavelength is 550 nm or more, preferably 600 nm or more, more preferably 650 nm or more, even more preferably 680 nm or more, and still more preferably 700 nm or more. (21) When the thickness of the environmentally friendly glass material is 3 mm, the transmittance at 800 to 850 nm is 75% or more, preferably the transmittance at 800 to 850 nm is 77% or more, and more preferably the transmittance at 800 to 850 nm is 80% or more; and / or when the thickness of the environmentally friendly glass material is 3 mm, the transmittance at 850 to 900 nm is 80% or more, preferably the transmittance at 850 to 900 nm is 82% or more, and more preferably the transmittance at 850 to 900 nm is 83% or more; and / or and / or the environmentally friendly glass material according to (9), wherein when the thickness of the environmentally friendly glass material is 3 mm, the transmittance from 900 to 1000 nm is 83% or more, preferably the transmittance from 900 to 1000 nm is 84% or more, and more preferably the transmittance from 900 to 1000 nm is 85% or more, when the thickness of the environmentally friendly glass material is 3 mm, the transmittance from 1000 to 2000 nm is 85% or more, preferably the transmittance from 1000 to 2000 nm is 86% or more, and more preferably the transmittance from 1000 to 2000 nm is 87% or more. (22) The environmentally friendly glass material has an acid resistance stability of Class 3 or higher, preferably Class 2 or higher, and more preferably Class 1; and / or a water resistance stability of Class 3 or higher, preferably Class 2 or higher, and more preferably Class 1; and / or a thermal expansion coefficient of 80×10 -7 / K or more, preferably 85×10 -7 / K or more, preferably 90×10 -7 / K or more, and more preferably 95×10 -7 / K or more. (23) A glass preform using the environmentally friendly glass material according to any one of (1) to (22). (24) A glass member using the environmentally friendly glass material according to any one of (1) to (22) or the glass preform according to (23). (25) A device comprising the environmentally friendly glass material according to any one of (1) to (22) and / or the glass member according to (24). (26) A method for producing an environmentally friendly glass material according to any one of (1) to (22), comprising the following steps: 1) Mix all the raw materials according to the component ratio of the environmentally friendly glass material, put the homogeneously mixed raw materials into a melting furnace, and melt them at 1300~1500℃ to form molten glass; 2) Stirring and homogenizing the molten glass; 3) Pouring or leaking the molten glass into a mold to form it; 4) The glass formed in step 3) is held at 470 to 600°C for 10 to 60 hours to develop color, or the glass formed in step 3) is further processed into a glass preform or a glass member, and then held at 470 to 600°C for 10 to 60 hours to develop color. (27) A method for producing an environmentally friendly glass material according to (26), wherein a compound salt, and / or a hydroxide, and / or an oxide, and / or a sulfide, and / or a selenide, and / or a fluoride, and / or an element is used as a raw material for the environmentally friendly glass material. Effect of the Invention
[0006] The beneficial effect of the present invention is that, through rational component design, the glass material of the present invention achieves ultraviolet and visible light blocking and high near-infrared transmittance while being environmentally friendly. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a curve graph showing the spectral transmittance of an environmentally friendly glass material according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the embodiments described below, and can be modified as appropriate within the scope of the object of the present invention. Furthermore, repeated explanations will be omitted as appropriate, but this does not limit the gist of the present invention. Hereinafter, the environmentally friendly glass material of the present invention may be referred to as glass.
[0009] [Environmentally friendly glass materials] The range of the components (constituent elements) of the environmentally friendly glass material of the present invention will be described below. In this specification, unless otherwise specified, the content of each component and the total content are expressed in weight % (wt%).
[0010] Numerical ranges set forth in this specification include upper and lower limits unless otherwise stated, and the terms "greater than or equal to" and "less than or equal to" include the endpoints, and all integers and fractions within the range, but are not limited to the specific values set forth when a range is limited. References to "and / or" in this specification are inclusive, e.g., "A and / or B" means A only, B only, or both A and B.
[0011] <Required and optional ingredients> SiO2 is one of the main components of glass. In the glass of the present invention, an appropriate amount of SiO2 stabilizes coloring and enables the glass to achieve the desired cut-off performance. Meanwhile, an appropriate amount of SiO2 enables the chemical stability of the glass to be increased. If the content of SiO2 is less than 35%, the cut-off performance of the glass will not meet the design requirements, and the chemical stability of the glass will rapidly decrease. Therefore, in the present invention, the lower limit of the content of SiO2 is 35%, preferably 40%, and more preferably 42%. If the content of SiO2 exceeds 80%, the melting temperature of the glass will rise rapidly, the volatilization of the coloring substance will increase, and the cut-off performance of the glass will decrease. At the same time, the high-temperature viscosity of the glass will rise rapidly, and the bubbles and inclusions in the product will rapidly increase. Therefore, the upper limit of the content of SiO2 in the present invention is 80%, preferably 75%, and more preferably 73%.
[0012] The B2O3 in the glass of the present invention improves the melting performance of the glass and enhances the intrinsic quality and chemical stability of the glass. However, the inventors have found through research that the B2O3 in the glass causes changes in the glass structure, increases the threshold for bonding of coloring substances, and reduces the cut-off ability of the glass. Therefore, if the cut-off ability of the glass meets the requirements, the glass may contain 10% or less B2O3, preferably 5% or less, more preferably 3% or less B2O3 to enhance the melting performance and chemical stability of the glass. In some implementations, it is even more preferable to not contain B2O3.
[0013] Through extensive experimental research, the present inventors have found that in some implementations, the water resistance stability of glass can be improved while optimizing the cutoff performance of the glass by making B2O3 / SiO2 0.23 or less, preferably B2O3 / SiO2 0.15 or less, and more preferably B2O3 / SiO2 0.1 or less.
[0014] ZnO in glass can improve the chemical stability of glass and reduce the high-temperature viscosity of glass. With the cooperation of SiO2, it can suppress the volatilization of coloring substances during the melting stage, and at the same time, promote the structural change of coloring substances, and improve the cut-off performance of glass. If the ZnO content is less than 5%, the cut-off performance of glass does not meet the requirements, and the chemical stability of glass is reduced. Therefore, the lower limit of the ZnO content is 5%, preferably 7%, and more preferably 9%. If the ZnO content exceeds 35%, the glass is easily devitrified, especially during the molding and annealing stages, and the near-infrared transmittance of glass is significantly reduced. Therefore, the upper limit of the ZnO content is 35%, preferably 30%, and more preferably 25%.
[0015] In some implementations of the present invention, if the value of ZnO / SiO2 is less than 0.07, the chemical stability of the glass does not meet the design requirements, and the cut-off ability of the glass is reduced. If the value of ZnO / SiO2 is 0.95 or more, non-colored substances in the glass are likely to be devitrified, and the near-infrared transmittance, particularly at 800 to 1000 nm, tends to decrease rapidly. Therefore, the value of ZnO / SiO2 is 0.07 to 0.95, more preferably 0.10 to 0.75, and even more preferably 0.15 to 0.60. In this case, the threshold for the generation of glass coloring substances can be lowered, contributing to the improvement of the cut-off performance and the near-infrared transmittance.
[0016] Li2O, Na2O, and K2O, which belong to the alkali metal oxides contained in the glass of the present invention, can reduce the high-temperature viscosity of the glass and reduce bubbles and inclusions in the glass. While reducing the high-temperature viscosity, they can increase the solubility of coloring substances and improve the cut-off performance of the glass. In addition, the alkali metal oxides can supply more free oxygen, realizing better cut-off performance and at the same time improving the near-infrared transmittance of the glass. However, if the content is less than 8%, the above effects are not significant, and on the other hand, the expansion coefficient of the glass becomes lower than the design target, and does not match well with materials with high hardness and high expansion coefficient. If the content exceeds 35%, the glass is prone to devitrification, the cut-off performance and near-infrared transmittance decrease, and the chemical stability also rapidly decreases. Therefore, the total content of the alkali metal oxides Li2O+Na2O+K2O is 8 to 35%, preferably 9 to 30%, and more preferably 10 to 22%.
[0017] Li2O has an excellent ability to reduce the high-temperature viscosity of glass, and is beneficial for improving the essential quality of glass. However, the inventors have found that Li ions have a strong ability to aggregate in glass and inhibit the structural change of coloring substances, thereby reducing the cut-off performance of the glass. In particular, if the content exceeds 5%, the glass cannot obtain the desired cut-off performance. Therefore, the content of Li2O is preferably 5% or less, more preferably 3% or less, and even more preferably 2% or less. In some implementations, it is even more preferable that the glass does not contain Li2O.
[0018] Na2O in glass can reduce the high-temperature viscosity of glass and reduce the threshold of structural change of coloring material. At the same time, it can improve the near-infrared transmittance of glass, increase the thermal expansion coefficient of glass, and facilitate the bonding of the glass of the present invention with high-strength transparent materials. If the content of Na2O is less than 5%, the near-infrared transmittance of glass does not meet the design requirements, the cut-off performance of glass is reduced, and the thermal expansion coefficient of glass is lower than the design requirements. Therefore, the lower limit of the content of Na2O is 5%, preferably 7%, and more preferably 8%. If the content of Na2O exceeds 25%, the chemical stability of glass is reduced, the glass is easily devitrified, the threshold of structural change of coloring material is increased, and the cut-off performance of glass is reduced. Therefore, the upper limit of the content of Na2O is 25%, preferably 22%, and more preferably 19%.
[0019] In this glass system, the role of K2O is similar to that of Na2O, but its ability to enhance near-infrared radiation is stronger than that of Na2O; on the other hand, its ability to reduce the chemical stability of the glass and its resistance to devitrification are stronger than those of Na2O. Therefore, the content of K2O is limited to 1 to 10%, preferably 2 to 8%, and more preferably 3 to 7%, from the viewpoint of optimizing the chemical stability, resistance to devitrification, and cutoff performance of the glass.
[0020] Al2O3 in glass can improve the chemical stability of glass, but it also causes a decrease in the cut-off performance of glass. If its content exceeds 5%, the cut-off performance of glass does not meet the design requirements. The content of Al2O3 is 5% or less, preferably 3% or less. If the chemical stability of glass is excessive, the content of Al2O3 is more preferably 1% or less.
[0021] MgO improves the chemical stability of glass. However, if the content exceeds 5%, the devitrification resistance of glass decreases, the cutoff ability of glass decreases, and the near-infrared transmittance also decreases. Therefore, the content of MgO is limited to 5% or less, preferably 3% or less, and more preferably 2% or less.
[0022] CaO improves the stability and devitrification resistance of glass and reduces the high-temperature viscosity. If its content exceeds 5%, it inhibits the structure formation of coloring substances and reduces the cut-off performance of glass. Therefore, the CaO content is limited to 5% or less, preferably 3% or less, and more preferably 2% or less.
[0023] The appropriate amount of BaO and SrO in glass can improve the chemical stability of glass, increase the hardness of glass, and improve the near-infrared transmittance of glass. However, if the content exceeds 10%, the fixing ability of the coloring material in glass may decrease, and the cut-off ability may decrease. Therefore, the contents of BaO and SrO are each limited to 10% or less, preferably 5% or less, and more preferably 2% or less.
[0024] F in glass increases the melting property of glass, suppresses the volatilization of coloring substances during the supply stage, and improves the cut-off performance of glass. However, if the content exceeds 5%, the high-temperature viscosity of glass drops sharply and coloring substances volatilize excessively. Therefore, from the viewpoint of environmental protection, the F content is 5% or less, preferably 3% or less, more preferably 1% or less, and even more preferably 0%.
[0025] Since S can form coloring substances with Sb, Ag, Ce, Sn, Te, V, Fe, etc. in the glass of the present invention, the glass has a cutoff absorption in the band before 500 to 720 nm. If the S content exceeds 8%, the glass is easily devitrified and the near-infrared transmittance drops sharply. If the S content is less than 0.2%, the cutoff performance of the glass does not satisfy the design requirements. Therefore, the S content is limited to 0.2 to 8%, preferably 0.5 to 7%, and more preferably 1 to 6%. The S content in the present invention is the content of sulfur that is completely converted to elemental sulfur among all sulfur-containing substances in the glass. In the present invention, S can be introduced by elemental sulfur and / or a sulfur-containing compound.
[0026] Since Se can form coloring substances with Sb, Ag, Ce, Sn, Te, V, Fe, etc. in the glass of the present invention, the glass generates cutoff absorption in the band before 650 to 1200 nm, and can be made into a glass with better cutoff performance than simple S or sulfides. If the content of Se exceeds 5%, the glass is easily devitrified and the near-infrared transmittance drops sharply. Therefore, when the cutoff performance satisfies the design requirements, the content of Se in the present glass system is 5% or less, preferably 4% or less, more preferably 3% or less, and even more preferably 0%. The content of Se in the present invention is the content of selenium that is completely converted to elemental selenium among all selenium-containing substances in the glass. In the present invention, Se can be introduced by elemental selenium and / or a selenium-containing compound.
[0027] Through extensive experimental research, the present invention has found that in some implementations, when the Se / S value exceeds 1.5, the transmittance of the glass at 800-1000 nm does not meet the design requirements. Therefore, the Se / S value is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.0 or less, and even more preferably 0.5 or less.
[0028] At least one of the components such as Sb, Ag, Ce, Sn, Te, V, and Fe in the glass of the present invention can form a colored compound with S and / or Se. If the total content of Sb+Ag+Ce+Sn+Te+V+Fe exceeds 10%, the glass is prone to devitrification, and the near-infrared transmittance drops sharply. If the total content of Sb+Ag+Ce+Sn+Te+V+Fe is less than 0.5%, colored substances are unlikely to be generated in the glass, and the cutoff performance as designed cannot be obtained. Therefore, the content of Sb+Ag+Ce+Sn+Te+V+Fe is 0.5 to 10%, preferably 0.8 to 9%, and more preferably 0.9 to 8%. The content of Sb+Ag+Ce+Sn+Te+V+Fe in the present invention means the total content of Sb in the Sb-containing material, Ag in the Ag-containing material, Ce in the Ce-containing material, Sn in the Sn-containing material, Te in the Te-containing material, V in the V-containing material, and Fe completely converted to elements in the Fe-containing material in the glass. Sb, Ag, Ce, Sn, Te, V, and Fe may be introduced by oxides, and / or sulfides, and / or selenides, and / or fluorides, and / or simple substances, and / or compound salts, and / or hydroxides, etc. In some implementations of the present invention, it is preferable to not include Sn and / or Te.
[0029] In some implementations of the present invention, when (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is less than 0.1, the near-infrared transmittance of the glass is significantly reduced, and when (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is more than 25.0, the cutoff performance of the glass is significantly reduced, and the devitrification resistance of the glass is also rapidly reduced. Therefore, the value of (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is preferably 0.1 to 25.0, more preferably 0.2 to 15.0, even more preferably 0.5 to 8.0, and even more preferably 1.0 to 5.0.
[0030] In some implementations of the present invention, there is a synergistic effect when Sb, Ag, Ce, Sn, Te, V, and Fe form coloring substances with anions in glass; when the value of (Ag+Ce+Sn+Te+V+Fe) / Sb is greater than 3.0, the near-infrared transmittance of the glass is significantly reduced. Therefore, it is preferable that the value of (Ag+Ce+Sn+Te+V+Fe) / Sb is 3.0 or less, more preferably 2.0 or less, even more preferably 1.0 or less, and even more preferably 0.8 or less.
[0031] In some implementations of the present invention, one or more of CuO, TiO2, and P2O5 can be additionally contained in the glass of the present invention in order to promote the formation of coloring substances. However, if the total content of CuO, TiO2, and P2O5 (CuO+TiO2+P2O5) exceeds 0.5%, the glass is particularly prone to devitrification, and the structure of the coloring substances changes negatively, so that the near-infrared transmittance is likely to decrease rapidly. Therefore, the content of CuO+TiO2+P2O5 is 0.5% or less. On the other hand, if CuO+TiO2+P2O5 is less than 0.0001%, the coloring substances can only be formed in the impurity defects in the glass, which may cause problems such as poor cut-off performance of the glass or poor coloring uniformity of the glass. Therefore, preferably, CuO+TiO2+P2O5 is 0.0001 to 0.5%, more preferably 0.0001 to 0.4%, and even more preferably 0.0001 to 0.3%. The contents of CuO, TiO2 and P2O5 in the present invention are not included in 100 wt% which is the content of all components other than CuO, TiO2 and P2O5 described in the present invention.
[0032] <Unnecessary ingredients> Due to environmental considerations, the glass of the present invention does not contain Cd, As or Pb. Here, "free" and "0%" mean that compounds, molecules, elements, etc. are not intentionally added as raw materials for the glass of the present invention; however, if there are small or trace amounts of specific impurities or components that are not intentionally added as raw materials and / or equipment for the production of glass in the final glass, this situation is also included in the scope of protection of the patent of the present invention.
[0033] The characteristics of the environmentally friendly glass material of the present invention will be described below.
[0034] <Cut-off performance> Using a spectrometer according to the method of GB / T7962.12-2010, the transmittance curve of 3mm glass sample at 300nm~2000nm is tested, and the transmittance of 5% is the cut-off wavelength. In the present invention, the higher the cut-off wavelength value of the glass, the better the cut-off performance, and the lower the cut-off wavelength value, the worse the cut-off performance.
[0035] In some implementations of the present invention, the cutoff wavelength of the environmentally friendly glass material is 550 nm or more, preferably 600 nm or more, more preferably 650 nm or more, even more preferably 680 nm or more, and even more preferably 700 nm or more.
[0036] <Near infrared transmittance> The transmittance curve of the glass in the range of 300nm to 2000nm of a 3mm glass sample is tested using a spectrometer according to the method of GB / T7962.12-2010, and the near-infrared transmittance in the present invention refers to the transmittance value in the range of 800nm to 2000nm. Note that, the near-infrared transmittance in the present invention refers to the lowest transmittance in the corresponding wavelength band range.
[0037] In some implementations of the present invention, the environmentally friendly glass material of the present invention has one or more of the following transmittances:
[0038] 1) The transmittance from 800 to 850 nm is 75% or more, preferably the transmittance from 800 to 850 nm is 77% or more, and more preferably the transmittance from 800 to 850 nm is 80% or more.
[0039] 2) The transmittance from 850 to 900 nm is 80% or more, preferably the transmittance from 850 to 900 nm is 82% or more, and more preferably the transmittance from 850 to 900 nm is 83% or more.
[0040] 3) The transmittance from 900 to 1000 nm is 83% or more, preferably the transmittance from 900 to 1000 nm is 84% or more, and more preferably the transmittance from 900 to 1000 nm is 85% or more.
[0041] 4) The transmittance from 1000 to 2000 nm is 85% or more, preferably the transmittance from 1000 to 2000 nm is 86% or more, and more preferably the transmittance from 1000 to 2000 nm is 87% or more.
[0042] <Acid resistance stability> Acid resistance of glass materials (D A ) (powder method) is tested in accordance with the method specified in GB / T 17129. Here, acid resistance is sometimes called acid resistance or acid stability.
[0043] In some implementations of the present invention, the acid stability (D A ) is class 3 or higher, preferably class 2 or higher, and more preferably class 1.
[0044] <Water resistance stability> Water resistance stability of glass materials (D W ) (powder method) is tested in accordance with the method specified in GB / T 17129. Here, water resistance is sometimes called water resistance or water stability.
[0045] In some implementations of the present invention, the water resistance stability (D W ) is class 3 or higher, preferably class 2 or higher, and more preferably class 1.
[0046] <Thermal expansion coefficient> The thermal expansion coefficient in the present invention refers to the average thermal expansion coefficient of glass at 20 to 300 ° C., and α 20-300℃ and is tested according to the method specified in GB / T7962.16-2010.
[0047] In some implementations of the present invention, the average thermal expansion coefficient (α 20-300℃ ) is 80 x 10-7 / K or more, preferably 85×10 -7 / K or more, preferably 90×10 -7 / K or more, and more preferably 95×10 -7 / K or higher.
[0048] [Manufacturing method] The method for producing the environmentally friendly glass material of the present invention includes the following steps: 1) Mix all the raw materials according to the component ratio of the environmentally friendly glass material, put the homogeneously mixed raw materials into a melting furnace, and melt them at 1300~1500℃ to form molten glass; 2) Stirring and homogenizing the molten glass; 3) Pouring or leaking the molten glass into a mold to form it; 4) The glass formed in step 3) is held at 470 to 600°C for 10 to 60 hours to develop color, or the glass formed in step 3) is further processed into a glass preform or a glass member, and then held at 470 to 600°C for 10 to 60 hours to develop color.
[0049] Furthermore, the raw materials for the above-mentioned environmentally friendly glass material may be composite salts (carbonates, sulfates, nitrates, etc.), and / or hydroxides, and / or oxides, and / or sulfides, and / or selenides, and / or fluorides, and / or simple substances.
[0050] [Glass preforms and glass components] A glass preform can be produced from the environmentally friendly glass material by compression molding means such as grinding or reheat forming, precision stamping, etc. That is, a glass preform can be produced by polishing and other mechanical processing of the environmentally friendly glass material, a glass preform can be produced by producing a preform for compression molding from the environmentally friendly glass material, reheat forming this preform and polishing it, or a glass preform can be produced by precision stamping the preform produced by polishing.
[0051] The means for producing the glass preform is not limited to the above means.
[0052] The glass preform and glass member of the present invention are both formed from the above-mentioned environmentally friendly glass material of the present invention. The glass preform of the present invention has the excellent properties of the environmentally friendly glass material, and the glass member of the present invention has the excellent properties of the environmentally friendly glass material, and can provide various valuable glass members such as filters, lenses, and prisms.
[0053] [device] The environmentally friendly glass material of the present invention and glass members formed therefrom can be used in the manufacture of optical filters, photographic devices, camera equipment, display equipment, surveillance equipment, electronic equipment, intelligent equipment, and the like.
[0054] Embodiment In order to further clearly describe and illustrate the technical solutions of the present invention, the following non-limiting embodiments 1 to 22 are provided.
[0055] In this embodiment, the manufacturing method of the environmentally friendly glass material described above is used to obtain an environmentally friendly glass material having the components shown in Tables 1 to 3. In addition, the properties of each glass were measured by the test methods described in the present invention, and the results are shown in Tables 1 to 3. [Table 1] [Table 2] [Table 3]
Claims
1. Its components, expressed in weight percent, are: SiO 2 35-80%; ZnO 5-35%; Na 2 O 5-25%; K 2 An environmentally friendly glass material that contains 1-10% O, 0.2-8% S, and 0.5-10% Sb+Ag+Ce+Sn+Te+V+Fe, and does not contain Cd.
2. Its components, expressed in weight percent, are: Li 2 O 0-5%; B 2 O 3 0-10%; Al 2 O 3 2. The environmentally friendly glass material according to claim 1, comprising: 0-5% of MgO; 0-5% of CaO; 0-5% of SrO; 0-10% of BaO; 0-5% of Se; and 0-5% of F.
3. Its components, expressed in weight percent, are: SiO 2 and / or ZnO in an amount of 7 to 30%; and / or Na 2 O 7-22%; and / or K 2 O 2-8%; and / or Li 2 O is 0 to 3%; and / or S is 0.5 to 7%; and / or Sb+Ag+Ce+Sn+Te+V+Fe is 0.8 to 9%; and / or B 2 O 3 and / or Al 2 O 3 and / or 0-3% MgO; and / or 0-3% CaO; and / or 0-5% SrO; and / or 0-5% BaO; and / or 0-4% Se; and / or 0-3% F.
4. Its components, expressed in weight percent, are: SiO 2 and / or ZnO in an amount of 9 to 25%; and / or Na 2 O 8-19%; and / or K 2 O 3-7%; and / or S 1-6%; and / or Sb+Ag+Ce+Sn+Te+V+Fe 0.9-8%; and / or Se 0-3%; and / or Li 2 O 0-2%; and / or B 2 O 3 and / or Al 2 O 3 and / or 0-2% MgO; and / or 0-2% CaO; and / or 0-2% SrO; and / or 0-2% BaO; and / or 0-1% F.
5. Its components expressed in weight percent are: CuO + TiO 2 +P 2 O 5 2. The environmentally friendly glass material according to claim 1, containing 0 to 0.5% of
6. Its components are expressed in weight percent: CuO + TiO 2 +P 2 O 5 The environmentally friendly glass material according to claim 1, containing 0.0001 to 0.3% of
7. The components are expressed in weight percent, 1) B 2 O 3 / SiO 2 is 0.23 or less, 2) ZnO / SiO 2 is 0.07 to 0.95, 3) Se / S is 1.5 or less, 4) (Sb+Ag+Ce+Sn+Te+V+Fe) / (Se+S) is 0.1 to 25.0, 5) (Ag+Ce+Sn+Te+V+Fe) / Sb is 3.0 or less, 6) Li 2 O + Na 2 O+K 2 2. The environmentally friendly glass material according to claim 1, wherein O is 8 to 35%.
8. The components are expressed in weight percent, 1) B 2 O 3 / SiO 2 is 0.15 or less, 2) ZnO / SiO 2 is 0.10 to 0.75, 3) Se / S is 1.0 or less, 4) (Sb+Ag+Ce+Sn+Te+V+Fe) / (Se+S) is 0.5 to 8.0, 5) (Ag+Ce+Sn+Te+V+Fe) / Sb is 2.0 or less, 6) I read 2 Oh+In 2 O+K 2 Oが9~30%、 2. The environmentally friendly glass material according to claim 1, which satisfies one or more of the above six conditions.
9. The components are expressed in weight percent, 1) B 2 O 3 / SiO 2 is 0.1 or less, 2) ZnO / SiO 2 is 0.15 to 0.60, 3) Se / S is 0.5 or less, 4) (Sb+Ag+Ce+Sn+Te+V+Fe) / (Se+S) is 1.0 to 5.0, 5) (Ag+Ce+Sn+Te+V+Fe) / Sb is 0.8 or less, 6) I read 2 Oh+In 2 O+K 2 Oが10~22%、 2. The environmentally friendly glass material according to claim 1, which satisfies one or more of the above six conditions.
10. 2. The environmentally friendly glass material according to claim 1, wherein, when the thickness of the environmentally friendly glass material is 3 mm, the cutoff wavelength is 600 nm or more, and / or the transmittance at 800 to 850 nm is 77% or more, and / or the transmittance at 850 to 900 nm is 82% or more, the transmittance at 900 to 1000 nm is 84% or more, and the transmittance at 1000 to 2000 nm is 86% or more.
11. 2. The environmentally friendly glass material according to claim 1, wherein, when the thickness of the environmentally friendly glass material is 3 mm, the cutoff wavelength is 700 nm or more, and / or the transmittance at 800 to 850 nm is 80% or more, and / or the transmittance at 850 to 900 nm is 83% or more, and / or the transmittance at 900 to 1000 nm is 85% or more, and / or the transmittance at 1000 to 2000 nm is 87% or more.
12. The environmentally friendly glass material has an acid resistance stability of Class 1; and / or a water resistance stability of Class 1; and / or a thermal expansion coefficient of 95×10 -7 2. The environmentally friendly glass material according to claim 1, wherein the temperature is 100° C. or higher.
13. A glass preform using the environmentally friendly glass material according to any one of claims 1 to 12.
14. A glass member using the environmentally friendly glass material according to any one of claims 1 to 12 or the glass preform according to claim 13.
15. A device comprising the environmentally friendly glass material according to any one of claims 1 to 12 and / or the glass member according to claim 14.
16. A method for producing an environmentally friendly glass material according to any one of claims 1 to 12, comprising the steps of: 1) Mix all the raw materials according to the component ratio of the environmentally friendly glass material, put the homogeneously mixed raw materials into a melting furnace, and melt them at 1300-1500℃ to form molten glass; 2) Stirring and homogenizing the molten glass; 3) Pouring or leaking the molten glass into a mold to form it; 4) The glass formed in step 3) is kept at 470 to 600°C for 10 to 60 hours to develop color, or the glass formed in step 3) is further processed into a glass preform or glass member, and then kept at 470 to 600°C for 10 to 60 hours to develop color. A manufacturing method for environmentally friendly glass materials.
17. 17. The method for producing an environmentally friendly glass material according to claim 16, wherein compound salts, and / or hydroxides, and / or oxides, and / or sulfides, and / or selenides, and / or fluorides, and / or simple substances are used as raw materials for the environmentally friendly glass material.
Citation Information
Patent Citations
JP1975040609A
Cover glass for watch
JP1982129838A
Optical colored glass, method of using the optical colored glass, and optical edge filter
JP2003119049A
Colored optical glass
JP2003160357A
Manufacturing process of microparticle dispersion glass and ultraviolet cut filter
JP2005206434A